Cross-cultural adaptation and psychometric assessment of the Portuguese language version of the Eating and Appraisal due to Emotions and Stress (EADES) Questionnaire in Brazilian adults - Santos, Priscila Carvalho [UNESP]; da Silva, Wanderson Roberto [UNESP]; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Springer Nature, 2021)
Purposes: To develop a Brazilian Portuguese version of the Eating and Appraisal due to Emotions and Stress (EADES) Questionnaire and estimate the psychometric properties of the EADES factorial model for young Brazilian adults and also to assess the association between EADES factors and age, body mass index (BMI), and economic level. Methods: The cross-cultural adaptation was performed using a standardized protocol. The psychometric properties were assessed separately for each sex. A structural model for each sex was developed to investigate the influence of age, economic level, and BMI on the EADES factors. Results: A total of 1240 participants completed the study [65.8% female, mean age 23.91 (SD = 5.03) years]. The EADES original factorial model did not present good psychometric properties. Then, a factorial model proposed for a Mexican sample was tested and a different model was fitted for each sex. The results showed that younger women have lower self-efficacy and self-confidence and poorer assessment of resources and coping skills. Women with a higher economic level have lower self-efficacy. Higher BMI was associated with lower self-efficacy and self-confidence in both sexes. Younger men have lower self-efficacy and poorer assessment of resources and coping skills. Conclusions: The Brazilian Portuguese version of the EADES provided valid and reliable data after refinement, and a different model was fitted for each sex. Sex, age, BMI, and economic level were significantly associated with the EADES factors. Level of evidence: Level V, descriptive cross-sectional study.
Keywords: Cross-cultural adaptation; Eating; Emotion; Psychometrics; Scale; Stress